2016
DOI: 10.1007/s11571-016-9399-8
|View full text |Cite
|
Sign up to set email alerts
|

The N170 component is sensitive to face-like stimuli: a study of Chinese Peking opera makeup

Abstract: The N170 component is considered a neural marker of face-sensitive processing. In the present study, the face-sensitive N170 component of event-related potentials (ERPs) was investigated with a modified oddball paradigm using a natural face (the standard stimulus), human- and animal-like makeup stimuli, scrambled control images that mixed human- and animal-like makeup pieces, and a grey control image. Nineteen participants were instructed to respond within 1000 ms by pressing the '' or '' key in response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Such preference in species with no parental care advocates the existence of a general mechanism to detect animacy in the natural environment [12]. Brain imaging such as functional magnetic resonance imaging, fMRI [13,14], magnetoencephalography, MEG [15], and electroencephalography, EEG [16][17][18][19] reveal that real faces and face-like nonface images activate similar occipito-temporal brain clusters with a hub in the fusiform face area, FFA (for review, see [20,21]). Face impression in such images usually arises spontaneously without any efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Such preference in species with no parental care advocates the existence of a general mechanism to detect animacy in the natural environment [12]. Brain imaging such as functional magnetic resonance imaging, fMRI [13,14], magnetoencephalography, MEG [15], and electroencephalography, EEG [16][17][18][19] reveal that real faces and face-like nonface images activate similar occipito-temporal brain clusters with a hub in the fusiform face area, FFA (for review, see [20,21]). Face impression in such images usually arises spontaneously without any efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on face perception of some face representations offer support to this postulate. Indeed, some studies showed that face representations are recognized as face categories even if they depict only schematic faces, emoticons, or items with mere hints of a face (Churches et al, 2014; Hadjikhani et al, 2009; Liu et al, 2016; Wheatley et al, 2011). This is attested by the fact that an increase in brain wave associated with face perception was observed in EEG studies (Eimer, 2011; Sagiv & Bentin, 2001).…”
mentioning
confidence: 99%
“…Previous studies also suggested that face-like objects were processed in the N170 component in the right hemisphere, through holistic processing (Caharel et al, 2013 ; Liu et al, 2016 ). Furthermore, Churches et al ( 2009 ) suggested that the amplitude of the N170 component in response to objects is affected by the face-likeness of the objects.…”
Section: Introductionmentioning
confidence: 90%